Rare Earth-Activated Silica-Based Nanocomposites. (23rd January 2008) - Armellini, C.; Chiappini, A.; Chiasera, A.; Ferrari, M.; Jestin, Y.; Mortier, M.; Moser, E.; Retoux, R.; Righini, G. C.
Abstract : Two different kinds of rare earth-activated glass-based nanocomposite photonic materials, which allow to tailor the spectroscopic properties of rare-earth ions: (i) Er 3+ -activated SiO2 -HfO2 waveguide glass ceramic, and (ii) core-shell-like structures of Er 3+ -activated silica spheres obtained by a seed growth method, are presented.